PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN KELOMPOK USAHA TANI DI DESA PED - Surata, I W.; Nindhia, T. G. T. (Buletin Udayana Mengabdi; Vol 15 No 1 (2016): Jurnal Udayana Mengabdi, 2016)
The objective of this study is to provide an understanding and skills to the community through counseling, training, and demonstration, in order to have the ability to develop its potential in agriculture and tourism. Ped village is one of the 16 villages in the District of Nusa Penida, Klungkung Regency, which has a variety of potential in the agricultural sector such as plantation, livestock, fisheries, seaweed, and tourism. However, this potential has not been managed optimally, because they do not have skills in utilizing appropriate technology. To solve these problems some activities have been conducted through the implementation of KKN PPM program that includes training and counseling of health care of pigs, the production of animal feed with fermentation technology, organic fertilizer, biogas, and techniques of drying seaweed. Implementation of these activities involved 10 speakers as an instructor or coach who has expertise that appropriate with the topic of training. All programs can be well implemented because of the participation and enthusiasm of the people. In addition to providing training and counseling, also has contributed in the form of effective microbial materials for improving the quality of animal feed, making pigsty, making para- para, vaccinating cattle, and vitamin-B complex. The results of these activities were expected can improve community empowerment in the form of strengthen the management system of farming group, and increase the productivity of agricultural products.
Keywords: empowerment, animal feed, organic fertilizer, biogas, seaweed.